2021
DOI: 10.1242/dev.198838
|View full text |Cite
|
Sign up to set email alerts
|

Arid1a regulates cell cycle exit of transit-amplifying cells by inhibiting the Aurka-Cdk1 axis in mouse incisor

Abstract: Stem cells self-renew or give rise to transit-amplifying cells (TACs) that differentiate into specific functional cell types. The fate determination of stem cells to TACs and their transition to fully differentiated progeny are precisely regulated to maintain tissue homeostasis. Arid1a, a core component of the switch/sucrose nonfermentable (SWI/SNF) complex, performs epigenetic regulation of stage- and tissue-specific genes that is indispensable for stem cell homeostasis and differentiation. However, the funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…In the signalling cascade, Aurka is the regulator at the very upstream and activates Plk1 (non-hub gene, in cluster 1) through phosphorylation, which is regulated by a series of events, and eventually activates the effector Cdk1 via dephosphorylation [ 45 ]. Previous studies show that the Aurka-Cdk1 axis is a part of a feedback activation loop at mitosis entry and its activity peaks during mitosis and mitotic exit [ 46 , 47 , 48 ]. Based on above evidence, the phoenix spheres may belong to the TACs population, hence exhibit active mitosis with involvement of the Aurka-Cdk1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…In the signalling cascade, Aurka is the regulator at the very upstream and activates Plk1 (non-hub gene, in cluster 1) through phosphorylation, which is regulated by a series of events, and eventually activates the effector Cdk1 via dephosphorylation [ 45 ]. Previous studies show that the Aurka-Cdk1 axis is a part of a feedback activation loop at mitosis entry and its activity peaks during mitosis and mitotic exit [ 46 , 47 , 48 ]. Based on above evidence, the phoenix spheres may belong to the TACs population, hence exhibit active mitosis with involvement of the Aurka-Cdk1 axis.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has also shown that MSCs in the proximal region of the adult incisor take about four weeks to populate the entire dental mesenchyme and reach the distal end of the incisor (19). This knowledge has provided the opportunity to measure the rate by which MSCs give rise to cells of the incisor mesenchyme, such as odontoblasts and dental pulp cells, which has facilitated the analysis of how genetic mutations, for example, may affect the migration of MSC progeny and ultimately affect the fate of these cells in supporting tissue homeostasis and repair (27,28). Similarly, the rate of odontoblast differentiation from the MSCs/TACs can also be measured.…”
Section: Epithelial and Mesenchymal Stem Cells In The Mouse Incisormentioning
confidence: 99%
“…Finally, because of the easy access to and well defined molecular markers in adult mouse incisors, we can measure the growth rate of the incisor and its ability to repair following injury. These analyses can be linked with the dynamic changes in MSCs or TACs in the proximal region of the incisor, making it possible to comprehensively evaluate the molecular and cellular processes involved in tissue homeostasis and repair (27,28).…”
Section: Epithelial and Mesenchymal Stem Cells In The Mouse Incisormentioning
confidence: 99%
See 2 more Smart Citations